Humidity‐Controlled Ultralow Power Layer‐by‐Layer Thinning, Nanopatterning and Bandgap Engineering of MoTe2. (12th November 2018) - Nagareddy, V. Karthik; Octon, Toby J.; Townsend, Nicola J.; Russo, Saverio; Craciun, Monica F.; Wright, C. David
Abstract: A highly effective laser thinning method is demonstrated to accurately control the thickness of MoTe2 layers. By utilizing the humidity present in the ambient atmosphere, multilayered MoTe2 films can be uniformly thinned all the way down to monolayer with layer‐by‐layer precision using an ultralow laser power density of 0.2 mW µm −2 . Localized bandgap engineering is also performed in MoTe2, by creating regions with different bandgaps on the same film, enabling the formation of lateral homojunctions with sub‐200 nm spatial resolution. Field‐effect transistors fabricated from these thinned layers exhibit significantly improved electrical properties with an order of magnitude increase in on/off current ratios, along with enhancements in on‐current and field‐effect mobility values. Thinned devices also exhibit the fastest photoresponse (45 µs) for an MoTe2 ‐based visible photodetector reported to date, along with a high photoresponsivity. A highly sensitive monolayer MoTe2 photodetector is also reported. These results demonstrate the efficiency of the presented thinning approach in producing high‐quality MoTe2 films for electronic and optoelectronic applications. Abstract : A precision, laser‐assisted, humidity‐controlled, layer‐by‐layer thinning method in 2D MoTe2 films is presented. Field effect transistors fabricated from thinned layers exhibit an order of magnitude increase in on/off current, enhanced field‐effect mobility, and the fastest photoresponse for (visible) MoTe2 photodetectors reported to date. Localized band gap engineering is also performed, with sub‐200 nm spatial resolution, via the creation of lateral homojunctions.